Separation and purification of Si from Sn-30Si alloy by electromagnetic semi-continuous directional solidification - Huang, Feng (2020)
Electromagnetic semi-continuous directional solidification (ESCDS) was employed to separate and purify Si from Sn-30Si alloy. The experimental results indicate that the enrichment of primary silicon reaches approximately 91% as the solidification rate is 1.5 mm/min high. While Ca and B are removed by segregation, the removal mechanism of Fe is proved to be the recombination of segregation and ferrosilicon impurity phase precipitation. Resulting from the increase of the ratio of surface area to the volume (S/V) of the molten pool, the impurity remove via volatilization was enhanced. The removal ratios of the main impurities in MG-Si such as Al, Fe, Ca, B and P reach 96.55%, 99.05%, 98.81%, 43.33% and 60.53%, respectively. Due to the effective separation and purification effect, high growth rate, low or even no crucible contamination and consumption, ESCDS shows the great potential to further reduce the Sn consumption during Sn-Si solvent refining and increase the purification efficiency.